Learning-Adjusted Years of Schooling : Defining A New Macro Measure of Education - Filmer, Deon; Rogers, Halsey; Angrist, Noam; Sabarwal, Shwetlena (World Bank, Washington, DC, 2018)
The standard summary metric of education-based human capital used in macro analyses—the average number of years of schooling in a population—is based only on quantity. But ignoring schooling quality turns out to be a major omission. As recent research shows, students in different countries who have completed the same number of years of school often have vastly different learning outcomes. This paper therefore proposes a new summary measure, Learning-Adjusted Years of Schooling (LAYS), that combines quantity and quality of schooling into a single easy-to-understand metric of progress. The cross-country comparisons produced by this measure are robust to different ways of adjusting for learning (for example, by using different international assessments or different summary learning indicators), and the assumptions and implications of LAYS are consistent with other evidence, including other approaches to quality adjustment. The paper argues that (1) LAYS improves on the standard metric, because it is a better predictor of important outcomes, and it improves incentives for policymakers; and (2) its virtues of simplicity and transparency make it a good candidate summary measure of education.